Genetic Variability of Five Provenances of Eboni - Restu, Muhammad; Naiem, Mohammad (Jurnal Natur Indonesia, 2007)
A research was conducted to determine genetic variability and structure of ebony either within provenances or within trees in the same provenance using isozyme analyses. Results of this study are expected to show genetic variability of ebony with different provenances. For the purpose of the study, five provenances of ebony (Maros,Barru, Sidrap, Malili, and Mamuju) were prepared. The isozyme analysis using electrophoresis was applied to determine the genetic variability. The obtained data were statistically analyzed using multivariate and dendrogram analyses with Numerical Taxonomy System (NTSYS) Program applying unwighted pairgroup method and arrithmetic average (UPGMA) approach. Results showed that the variability of genetic provenances of ebony were less than any other tree species. Among the existing provenances, Barru dan Mamuju showed higher genetic variability compared to other provenances. Ebony provenance was generally found to homozygously increase or to performinbreeding. The genetic variability of ebony was mostly derived from the variability in population (95.4%). Grouping individual trees based on their provenances indicated that Malili provenance showed closed relationship to Maros provenance, whilst Mamuju provenance showed closed relationship to Barru and Sidrap provenances.